Development of functional beverages from blends of ficus deltoidea leaves and brown rice powders / Nur Ain Sabrina Azmi - Azmi, Nur Ain Sabrina (2022)
Functional foods and beverages offer a promising opportunity to improve healthcare awareness of people among Malaysian. Ficus deltoidea (Ficus: Moraceae) has great potential as a functional food or beverage. Administration of this herb has been reported to reduce hyperglycemia and increase insulin secretion in diabetic rats and humans. However, the potential benefits of adding F. deltoidea to food or beverage products such as brown rice remain to be investigated. Brown rice is a wholegrain food used as functional food or beverage in Asian nations to meet dietary and nutritional needs. The study primarily aimed to develop a new beverage formulation with the addition of F.deltoidea into brown rice and to examine the phyto-physicochemical profile, antioxidant properties, safety and consumer acceptance of the formulation. The new beverage formulations were prepared by mixing the F. deltoidea leaves powder with a commercial brown rice beverage product in two different ratios (2.5:32.5 and 5.0:30.0g). The formulated beverages were subjected to physicochemical and phyto chemical analyses. The antioxidant properties of the formulated beverage were measured using FRAP and DPPH assays. The acute toxicity study was conducted for 14 days to determine the safety of F. deltoidea-added formulations. Consumer acceptance on the appearance, color, aroma, taste, aftertaste and overall acceptability was assesse dutilising a 9-point hedonic scale. The results showed, for the first time, that adding F.deltoidea to brown rice beverage significantly decreased (p<0.05) the pH and increased(p<0.05) the moisture content, ash, and viscosity. The formulation with higher F.deltoidea was associated with lighter, greener and yellower in color. The total phenolic,flavonoid, and tannin content have also significantly increased (p<0.05) in F. deltoidei added formulations. Adding F. deltoidea to a brown rice beverage caused a significantincrease (p<0.05) in antioxidant activity. The oral LD50 of F. deltoidea-addedformulation was higher than 2000 mg/kg body weight. The sensory evaluations showed that the new formulation beverages were accepted by the consumer with the value of mean scores range for each parameter were higher than 5.0. In conclusion, these results suggest that adding F. deltoidea leaves to brown rice is safe to consume and improved the phyto-physicochemical profile, antioxidant activities, and consumers’ acceptance of the products.